Development of Video Tutorial-Based Learning Media in Basic Beauty Lessons - Zuda, Gholiya ghiska Putri; Rahmiati, Rahmiati (JURNAL PENDIDIKAN DAN KELUARGA, 2024)
Manual facial skin care is a material that is learned in basic beauty subjects. This study aims to develop learning media based on video tutorials on facial skin care manually at SMK Negeri 7 Padang. This research will measure the validity, practicality and effectiveness of the results of the development. This research is a type of R&D research and development, in this study it is necessary to follow the 4-D stages. The data collection instrument used in this study was a questionnaire as a validation assessment to material and media experts as well as practicality tests, and pretest and posttest questions to measure the level of effectiveness, data analysis using percentages with predetermined categories. The research sample was 30 students of class X Beauty Management at SMK Negeri 7 Padang for the academic year 2021/2022. The results of media design validation are 0.86 with a very valid category and 0.88 for material validation with a very valid category. Practical results obtained from student responses of 95.56% in the very practical category and practicality values obtained from teacher responses of 94.2% in the very practical category. The results of the effectiveness test obtained an average pretest value of 32.33 and an average posttest score of 85.00 with the result of a gain value of 0.77 which means that the developed media is very effective in improving students' abilities. From these results, the video tutorial-based learning media can be said to be valid, practical and effective to be used as teaching materials in the classroom. The suggestions that the researchers gave related to the results of this study were to teachers and students to be able to use this learning video media as a reference in classroom learning.